2002
DOI: 10.1046/j.1365-313x.2002.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a specialized cDNA library from plant cells isolated by laser capture microdissection: toward comprehensive analysis of the genes expressed in the rice phloem

Abstract: SummaryLaser capture microdissection (LCM) is a powerful system which allows the isolation of selectively targeted cells from a tissue section for the analysis of gene-expression profiles of individual cells. The technique has been successfully used for the isolation of specific mammalian cells, mainly cancer cells. However, LCM has never been reported to be applied to the gene expression analysis of plant cells. We used a modified LCM system and successfully applied it to target and isolate phloem cells of ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(138 citation statements)
references
References 15 publications
1
134
0
3
Order By: Relevance
“…None of the previously published cell-type-specific transcriptome analyses in plants (Asano et al, 2002;Birnbaum et al, 2003;Nakazono et al, 2003) dissected the root pericycle. Our analyses identified 90 genes that were preferentially expressed in the wild-type pericycle and 73 genes that were preferentially expressed in the rum1 pericycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the previously published cell-type-specific transcriptome analyses in plants (Asano et al, 2002;Birnbaum et al, 2003;Nakazono et al, 2003) dissected the root pericycle. Our analyses identified 90 genes that were preferentially expressed in the wild-type pericycle and 73 genes that were preferentially expressed in the rum1 pericycle.…”
Section: Discussionmentioning
confidence: 99%
“…Such microarray experiments provide average gene expression profiles of all cells in an organ and may potentially mask differential gene expression in a particular cell type. Laser capture microdissection (LCM) technology allows for the analysis of cell-type-specific gene expression profiles (Asano et al, 2002;Kerk et al, 2003;Nakazono et al, 2003). In this approach, frozen or fixed cells of interest are physically linked to a thermoplastic film with a low-power laser beam.…”
mentioning
confidence: 99%
“…nucleic acids, proteins and/or metabolites) from the harvested cells. The preparation of plant samples has been clearly illustrated in several original papers (Asano et al 2002;Kerk et al 2003;Klink et al 2005;Inada and Wildermurth 2005;Tang et al 2006;Cai and Lashbrook 2006) and in several reviews (Day et al 2005(Day et al , 2006Nelson et al 2006;Balestrini and Bonfante 2008;). Two methods have been utilized to prepare sample sections for LM: cryosectioning and paraffin sectioning.…”
Section: How Laser Microdissection Operatesmentioning
confidence: 99%
“…The preparation of frozen sections of more mature or vacuolated plant material generally requires fixation as well as a cryoprotectant treatment, such as sucrose, in order to alleviate the tissue damage caused by freezing. The application of this method has so far been limited to prepare a few plant tissues for LM (Asano et al 2002;Nakazono et al 2003;Casson et al 2005;Woll et al 2005). As an alternative, where a more satisfactory preservation of tissue histology is required for target identification (i.e.…”
Section: How Laser Microdissection Operatesmentioning
confidence: 99%
“…Whereas hundreds of RNAs have been identified in phloem (Asano et al, 2002;Vilaine et al 2003;Doering-Saad et al 2006;Omid et al 2007), only six have been confirmed via grafting experiments to be transported . Of these, CmGAIP, CmNACP, and CmPP16 are from Cucurbita maxima (Haywood et al 2005;Ruiz-Medrano et al 1999;Xoconostle-Cazares et al 1999), DELLA-GAI is from Arabidopsis (Haywood et al 2005), PFP-LeT6 is from tomato (Kim et al 2001), and StBEL5 is from potato (Banerjee et al 2006).…”
Section: Introductionmentioning
confidence: 99%